Scheduled Castes, Conversions and Socio- economic differentials: A Comparative Study of Two Social Groups in Maharashtra State - D C, Kirtiraj (Journal of International Buddhist Studies, 2016)
The Scheduled castes in India constitute 16.2 per cent of India’s total population and their presence can be found in all over India with different proportions. The potential of Buddhism as an instrument of social change and its sociological relevance to address a social problem (Untouchability) was well realized by Dr. Ambedkar and he appealed to all downtrodden and oppressed people to embrace Buddhism for their emancipations and to live a life with dignity and respect. Of the 59 SCs in Maharshtra only the Mahars (Neo-Buddhist) got converted into Buddhism in 1956. The other two dominant SCs in Maharashtra namely Matang and Chamar preferred to remain in the old Hindu fold as Hindu Dalits. The influence of Buddhism on Neo-Buddhist is not restricted to its spiritual realm alone but it is helping the people to their all-round development in all spheres of life It has brought the psychological changes and changed their life styles.(Kurne, 1997, Sharma, 2003, Beltz, 2005, ).It is now a well-known fact that there is a wide Socio-economic disparity between the converted and non-converted scheduled castes in Maharashtra state. The present study tries to find out the reasons behind their disparity and to what extent the conversion to Buddhism as an intervention has helped or not helped to the converted formerly untouchable castes.